Formulasi Hukum Penanggulangan Malpraktik Kedokteran - Priharto Adi (Universitas Syiah Kuala, 2013)
ABSTRACT: Indonesia legal system has a component of legal substance, namely criminal law, civil, and administrative laws does not recognized malpractice. The main rule is on the Act Number 23, 1992. This paper would like to explore (1) the policy formula of criminal law nowadays in suppressing medical malpractice. (2) the policy formula of criminal law in the future in overcoming such crime. The method applies is juridical comparative that is by exploring or analyzing secondary data gathered from secondary sources. This is descriptive analytical research. The data are then described and constructed the statement in document and in the act. The research reveals that punishment on corporation is limited to the violation of practice license by a doctor. In KUHP, the Act Number 36, 2009 regarding Health, the Act Number 29, 2004 regarding Doctor Practice after the decision of Constitutional Court is not regulated specially or the terms of malpractice is not recognized. Upcoming formula policy should be regulated regarding corporate liability in terms of medical practicing bringing loss for patients as the conduct of malpractice by doctors. Legal Formula on Suppressing Medical Malpractice